Recruiting and retaining bachelor qualified nurses in German hospitals (BSN4Hospital): protocol of a mixed-methods design - Maier, Claudia B; Köppen, Julia; Kleine, Joan; McHugh, Matthew D; Sermeus, Walter; Aiken, Linda H (BMJ open, 2023)
IntroductionMany countries in Europe are facing a shortage of nurses and seek effective recruitment and retention strategies. The nursing workforce is increasingly diverse in its educational background, ranging from 3-year vocational training (diploma) to bachelor and master educated nurses. This study analyses recruitment and retention strategies for academically educated nurses (minimum bachelor), including intention to leave, job satisfaction and work engagement compared with diploma nurses in innovative German hospitals; it explores recruitment and retention challenges and opportunities, and identifies lessons on recruitment and retention taking an international perspective.Methods and analysisThe study will apply a convergent mixed-methods design, including qualitative and quantitative methods. The qualitative study will include semistructured interviews among hospital managers, nurses, students and stakeholders in Germany. In addition, expert interviews will be conducted internationally in countries with a higher proportion of bachelor/master nurses in hospitals. The quantitative, cross-sectional study will consist of a survey among professional nurses (bachelor/master, diploma nurses) in German hospitals. Study settings are hospitals with a higher-than-average proportion of bachelor nurses or relevant recruitment, work environment or retention strategies in place. Analyses will be conducted in several phases, first in parallel, then combined via triangulation: the parallel analysis technique will analyse the qualitative and quantitative data separately via content analyses (interviews) and descriptive, bivariate and multivariate analyses (survey). Subsequently, data sources will be collectively analysed via a triangulation matrix focusing on developing thematic exploratory clusters at three systemic levels: microlevel, mesolevel and macrolevel. The analyses will be relevant for generating lessons for clinical nursing, management and policy in Germany and internationally.Ethics and disseminationEthics approval was obtained by the Charité Ethics Committee.Several dissemination channels will be used, including publications and presentations, for the scientific community, nursing management, clinical nurses and the wider public in Germany and internationally.